Building resilient and responsive research collaborations to tackle antimicrobial resistance—Lessons learnt from India, South Africa, and UK. (November 2020) - Veepanattu, P.; Singh, S.; Mendelson, M.; Nampoothiri, V.; Edathadatil, F.; Surendran, S; Bonaconsa, C.; Mbamalu, O.; Ahuja, S.; Birgand, G.; Tarrant, C.; Sevdalis, N.; et al.
Highlights: Capacity building for research and implementation is key to operationalzing concerted and sustained strategies for addressing antimicrobial resistance. Reciprocal and long-term partnerships between high-income and low- and middle-income countries can successfully develop robust, agile, and flexible antimicrobial stewardship research and implementation teams. Capacity building in AMR, when supported by adequate funding to ensure investment in the workforce and infrastructure, can result in sustainable and resilient AMS programmes. Abstract: Research, collaboration, and knowledge exchange are critical to global efforts to tackle antimicrobial resistance (AMR). Different healthcare economies are faced with different challenges in implementing effective strategies to address AMR. Building effective capacity for research to inform AMR-related strategies and policies is recognised as an important contributor to success. Interdisciplinary, intersector, as well as international collaborations are needed to span global to local efforts to tackle AMR. The development of reciprocal, long-term partnerships between collaborators in high-income and in low- and middle-income countries (LMICs) needs to be built on principles of capacity building. Using case studies spanning local and international research collaborations to codesign, implement, and evaluate strategies to tackle AMR, we have evaluated and build upon the ESSENCE criteria for capacity building in LMICs. The first case study describes the local codesign and implementation of antimicrobial stewardship (AMS) in the state of Kerala in India. The second case study describes an international research collaboration investigating AMR surgical patient pathways in India, the UK, and South Africa. We describe the steps undertaken to develop robust, agile, and flexible AMS research and implementation teams. Notably, investing in capacity building ensured that the programmes described in these case studies were sustained through the current severe acute respiratory syndrome coronavirus pandemic. Describing the strategies adopted by a local and an international collaboration to tackle AMR, we provide a model for capacity building in LMICs that can support sustainable and agile AMS programmes.